FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERCULOSIS PARU DI POLI PARU RUMAH SAKIT UMUM DATU BERU KABUPATEN ACEH TENGAH - Hudnah Hudnah; Lia Muslima (Universitas Prima Indonesia, 2023)
Based on the results obtained by the World Health Organization (WHO), the estimated number of TB cases is about two billion people out of a third of the world's population affected by pulmonary TB basil and half the world's population dies from tb disease, especially in developing countries. This study aims to find out the Factors Related to Pulmonary Tuberculosis Incidence in Datu Beru General Hospital, Central Aceh District.. This type of research is analytical with cross sectional design. The population in this study is all patients who visited Poli Paru RSU Datu Beru in 2020 as many as 181 population determined by slovin formula amounted to 64 respondents. Sampling is done by accidental sampling that is sampling by chance meet. The research was conducted from 12 to 22 October 2020 using questionnaires. From the results of this study showed that from the incidence of pulmonary tuberculosis the majority of respondents had pulmonary tuberculosis as many as 46 respondents (71.9%), from the majority of respondents of male gender as many as 39 respondents (60.9%), from the age of the majority of respondents aged adults (20-35 years) as many as 26 respondents (40.6%), from socioeconomic respondents had a low socioeconomic as much as 35 respondents (54.7%) , and from smoking habits the majority of respondents had smoking habits as many as 37 respondents (57.8%). There is a relationship between gender and pulmonary tuberculosis incidence with P value 0.005, there is a relationship between age and pulmonary tuberculosis incidence with P value 0.001, there is a relationship between socioeconomic and pulmonary tuberculosis incidence with P value 0.001, and there is a relationship between smoking habit and pulmonary tuberculosis incidence with P value 0.013. It is recommended to the public to be able to prevent lung tuberculosis early.